Why Discovery of PSA was not Granted a Nobel Prize? - ÖZMAN, Oktay (Urology Journal, 2024)
This essay draws attention to the prostate-specific antigen (PSA) discovery's lack of Nobel Prize acknowledgement despite its significance for prostate cancer (PCa) clinical practice. The Nobel Prize committee gives more weight to discoveries in basic research than to applications in medicine, which may account for PSA's lack of recognition. The prize has been dominated by the identification of cancer-causing viruses. Considering the subject from our -urologists- side, numerous pioneer researchers have uncovered PSA's presence and function, and its overuse in PCa screening has sparked debates about issues like overdiagnosis and overtreatment. We must concur that the factors contributing to PSA's underappreciation include the lack of a clear pioneer in its discovery and the contradictory opinions around its use. As a conclusion, PSA may have to wait for a better application before it receives recognition in the Nobel Prize.